Dissolved Organic Matter (DOM) in the open Mediterranean Sea. I. Basin–wide distribution and drivers of chromophoric DOM. (July 2018) - Catalá, Teresa S.; Martínez-Pérez, Alba María; Nieto-Cid, Mar; Álvarez, Marta; Otero, Jaime; Emelianov, Mikhail; Reche, Isabel; Arístegui, Javier; Álvarez-Salgado, Xosé Antón
Highlights: Basin–wide variability of DOC and a254 is explained by AOU in surface waters. Basin–wide variability of a325, S275–295 and SR is explained by temperature in surface waters. Water mass mixing explains the basin-wide variability of DOC and CDOM in deep waters. The consumption of colored substances absorbing at 325 nm prevails in the MedSea. a254 has revealed as an excellent proxy to the DOC concentration in the MedSea. Abstract: Chromophoric dissolved organic matter (CDOM) in the open Mediterranean Sea (MedSea) is barely documented, remaining the basin–wide patterns in intermediate and deep waters still enigmatic. Here, full–depth distributions of CDOM absorption coefficients and spectral slopes recorded during the HOTMIX 2014 cruise are presented and their respective environmental drivers resolved. General Additive Models (GAMs) in surface waters and Optimum MultiParameter (OMP) water mass analysis in deep waters were applied. In the surface, apparent oxygen utilisation (AOU), a proxy to cumulative net community respiration, explained most of the variability of dissolved organic carbon (DOC) and the absorption coefficient at 254 nm ( a 254 ), whereas the absorption coefficient at 325 nm ( a 325 ), and the spectral slopes were mostly explained by potential temperature, a proxy to stratification and solar radiation, indicating that both water column stability and photobleaching may drive the variability of the UV–A absorbing CDOM components. In deep waters, the effect of water mass mixing and basin–scale mineralization were discerned from local mineralization processes. Water mass mixing and basin–scale mineralization contributed more substantially to explain the variability of DOC, a 254 and a 325 (82–91%) than the variability of the spectral slopes (35–64%). Local mineralization processes indicate that DOC and CDOM play a more relevant role in the carbon cycle in the Eastern (EastMed) than in the Western (WestMed) Mediterranean: whereas DOC contributed to 66 ± 10% of the oxygen demand in the EastMed, it represented only 24 ± 4% in the WestMed. Independently of basins and layers, a 254 revealed as an excellent proxy to the concentration of DOC in the MedSea. Also, the unexpected inverse relationship of a 325 with AOU indicates that the consumption of the UV–A absorbing CDOM fraction prevails over their production.